Challenges of Choosing Thesis Title in Postgraduate Nursing Students: A Qualitative Study - Maryam Khoshbakht Pishkhani; Farahnaz Mohammadi Shahboulaghi; Kobra Ghorbanzadeh; Manijeh Dehi Aroogh; Nazila Vosoghi (Mashhad University of Medical Sciences, 2022)
Background: The process of conducting a student thesis has the stages among which selecting the title is undoubtedly the most important one. Students are faced with numerous challenges at this stage. The aim of this study was to determine the challenges faced by postgraduate nursing students regarding thesis title selection.Methods: This qualitative study was conducted using the conventional qualitative content analysis approach and purposive sampling method in 2017. Postgraduate nursing students of Tehran University of Social Welfare and Rehabilitation Sciences who were willing to participate in the study were interviewed using semi-structured interviews. Sampling was done using purposeful sampling and continued until data saturation.Results: Totally, 14 students with a mean age of 27.35± 3.43 participated in this study. All students were female.  Following data analysis, three categories, seven subcategories, and 245 cods emerged. The main categories extracted in this study included educational, systemic, and individual factors.Conclusion: According to the results of this study, paying attention to and alleviating educational, systemic, and individual challenges in choosing the appropriate thesis title seems necessary in order to accomplish the research process. Therefore, providing the necessary training, practical guidance from professors and advisors, explaining appropriate strategies in choosing the title, and enabling students in this field can play an influential role in eliminating these challenges.